2013
DOI: 10.4317/medoral.18831
|View full text |Cite
|
Sign up to set email alerts
|

Caries arresting effect of silver diamine fluoride on dentine carious lesion with S. mutans and L. acidophilus dual-species cariogenic biofilm

Abstract: Objectives: This in vitro study investigated the effects of silver diamine fluoride (SDF) on dentine carious lesion with cariogenic biofilm. Study Design: Thirty human dentine blocks were inoculated with Streptococcus mutans and Lactobacillus acidophilus dual-species biofilm to create carious lesion. They were equally divided into test and control group to receive topical application of SDF and water. After incubation anaerobically using micro-well plate at 37oC for 7 days, the biofilms were evaluated for kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 28 publications
4
127
2
9
Order By: Relevance
“…Laboratory studies have illustrated that the topical application of a 38% SDF solution can inhibit the growth of cariogenic biofilms [6,7,8]. It has been suggested that 38% SDF possesses a strong inhibitory effect on the action of cysteine cathepsins [18] and matrix metalloproteinase [19], which are closely related to the collagen degradation of dentine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies have illustrated that the topical application of a 38% SDF solution can inhibit the growth of cariogenic biofilms [6,7,8]. It has been suggested that 38% SDF possesses a strong inhibitory effect on the action of cysteine cathepsins [18] and matrix metalloproteinase [19], which are closely related to the collagen degradation of dentine.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that silver diamine fluoride (SDF) has an intense antibacterial effect on cariogenic bacteria and can inhibit the growth of multi-species cariogenic biofilms on tooth surfaces [6,7,8]. SDF is a topical fluoride which is often used in high concentration (38%) for preventing and arresting dental caries [9].…”
Section: Introductionmentioning
confidence: 99%
“…What is currently understood is that the fluoride component strengthens the tooth structure under attack by the acid byproducts of bacterial metabolism, 15 decreasing its solubility, but SDF may also interfere with the biofilm, killing bacteria that cause the local environmental imbalance that demineralizes dental tissues. 16 Thus, SDF becomes one of the tools available to address caries by modifying the bacterial actions on the tissue while enhancing remineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Among treatments of NaF, acidulated phosphate fluoride (APF), and silver diamine fluoride (SDF), SDF was the most effective 3,4) . It is unique in terms of anti-bacterial [5][6][7] and anti-enzymatic effects 8) with silver ions (Ag + ) in addition to the demineralization inhibition. These higher efficacies of SDF would be attributed to high concentrations of Ag (25.5%) and fluoride (44,880 ppm), leading to the acquisition of these ions on and into the dentin tissue 9) .…”
Section: Introductionmentioning
confidence: 99%